Odpowiedź :
Odpowiedź:
a) -2/3
b) 20/81
c) 9/5
Szczegółowe wyjaśnienie:
Skorzystamy z tożsamości trygonometrycznej:
[tex]\sin^2x+\cos^2x=1\to\cos^x=1-\sin^2x[/tex]
Dane:
[tex]\sin\alpha=\dfrac{2}{3}[/tex]
wówczas:
[tex]\cos^2\alpha=1-\left(\dfrac{2}{3}\right)^2=1-\dfrac{4}{9}=\dfrac{5}{9}[/tex]
a)
[tex]1-3\cos^2\alpha=1-3\!\!\!\!\diagup^1\cdot\dfrac{5}{9\!\!\!\!\diagup_3}=\dfrac{3}{3}-\dfrac{5}{3}=-\dfrac{2}{3}[/tex]
b)
[tex]\cos^2\alpha-\cos^4\alpha=\cos^2\alpha(1-\cos^2\alpha)=\cos^2\alpha\sin^2\alpha\\\\=\dfrac{5}{9}\cdot\left(\dfrac{2}{3}\right)^2=\dfrac{5}{9}\cdot\dfrac{4}{9}=\dfrac{20}{81}[/tex]
c)
[tex]\dfrac{\sqrt{1+\text{tg}^2\alpha}}{\cos\alpha}}=\dfrac{\sqrt{1+\left(\frac{\sin\alpha}{\cos\alpha}\right)^2}}{\cos\alpha}=\dfrac{\sqrt{1+\frac{\sin^2\alpha}{\cos^2\alpha}}}{\cos\alpha}=\dfrac{\sqrt{\frac{\cos^2\alpha}{\cos^2\alpha}+\frac{\sin^2\alpha}{\cos^2\alpha}}}{\cos\alpha}\\\\=\dfrac{\sqrt{\frac{\cos^2\alpha+\sin^2\alpha}{\cos^2\alpha}}}{\cos\alpha}=\dfrac{\sqrt{\frac{1}{\cos^2\alpha}}}{\cos\alpha}=\dfrac{\frac{1}{\cos\alpha}}{\cos\alpha}=\dfrac{1}{\cos^2\alpha}=\dfrac{1}{\frac{5}{9}}=\dfrac{9}{5}[/tex]
skorzystaliśmy z tożsamości trygonometrycznej
[tex]\text{tg}x=\dfrac{\sin x}{\cos x}[/tex]
oraz z tego, że [tex]\alpha\in(0^o,\ 90^o)[/tex], to [tex]\cos\alpha>0[/tex].
Stąd [tex]\sqrt{\dfrac{1}{\cos^2\alpha}}=\dfrac{1}{\cos\alpha}[/tex], a nie [tex]\left|\dfrac{1}{\cos\alpha}\right|[/tex]